Antecedent and Cumulative Rainfall as Thresholds in Detecting Possible Landslide Occurrence - Khalid N.H.N.; Usman F.; Omar R.C.; Norhisham S. (Springer Science and Business Media Deutschland GmbH, 2023)
Disasters; Rain; Antecedent rainfall; Cumulative rainfall; Landslide monitoring; Natural disasters; Predictive models; Public awareness; Slope failure; Study areas; Threshold; Threshold-value; Landslides